Proceedings of the Conference on Human Language Technology and Empirical Methods in Natural Language Processing - HLT '05 2005
DOI: 10.3115/1220575.1220615
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced answer type inference from questions using sequential models

Abstract: Question classification is an important step in factual question answering (QA) and other dialog systems. Several attempts have been made to apply statistical machine learning approaches, including Support Vector Machines (SVMs) with sophisticated features and kernels. Curiously, the payoff beyond a simple bag-ofwords representation has been small. We show that most questions reveal their class through a short contiguous token subsequence, which we call its informer span. Perfect knowledge of informer spans ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 13 publications
(19 reference statements)
2
32
1
Order By: Relevance
“…Krishnan et al [3] also showed that the effect of the features chosen by a CRF model varies significantly depending on the accuracy of the CRF model. In a machine learning approach, feature selection is an optimization problem that involves choosing an appropriate feature subset.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Krishnan et al [3] also showed that the effect of the features chosen by a CRF model varies significantly depending on the accuracy of the CRF model. In a machine learning approach, feature selection is an optimization problem that involves choosing an appropriate feature subset.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works [1,4,8] have shown that CRFs have a consistent advantage over traditional Hidden Markov Models (HMMs) and Maximum Entropy Markov Models (MEMMs) [6] in the face of many redundant features. Krishnan et al [3] reported that they achieved 85%-87% accuracy of question informer prediction by using CRF model with a set of features.…”
Section: Conditional Random Fields (Crfs)mentioning
confidence: 99%
See 3 more Smart Citations